On the Pendant Regular Domination Number of a Graph - Ajithkumara; Puttaswamy; Puneeth, S. (Communications in Mathematics and Applications, 2025)
This paper introduces and explores a novel domination parameter in graph theory, termed the pendant regular domination number. We initiate a foundational study by determining the exact values of this parameter for several standard and well-known graph families, including paths, cycles, stars, and complete graphs. In addition, few fundamental bounds are deduced and the behavior of the pendant regular domination number is examined under various graph operations such as the corona, join, and Cartesian product.